The EU regulatory framework for market risk and prudent valuation: Are the rules too procyclical? Evidence from the COVID-19 pandemic and the 2022 global energy crisis - Stéphane Boivin; Marco Giovanni Crotti; Despo Malikkidou (European Banking Authority, 2023)
The 2020 COVID-19 pandemic crisis and the 2022 global energy crisis consecutive to Russia's aggression against Ukraine have been unprecedented in several aspects. In the European Union (EU), national governments, as well as European bodies put in place several relief measures to support the EU economy. However, the regulatory and supervisory responses in relation to prudential matters have been very different in these two crises. In this paper, we first assess the impact of the two crises on the capital requirements related to traded risk and discuss the issue of procyclicality in the regulatory framework. We then analyse and compare the regulatory measures taken by the legislators and by the European Banking Authority (EBA). We finally identify how the regulatory framework is set to change to address the drawbacks that became evident during the recent crises.
Keywords: G21; G28; G32; C00; 330; Market risk; Prudent valuation; procyclicality; capital requirements; FRTB